The cardio‐respiratory effects of passive heating and the human thermoneutral zone. Issue 16 (19th August 2021) - Henderson, Mary E.T.; Brayson, Daniel; Halsey, Lewis G
Abstract: The thermoneutral zone (TNZ) defines the range of ambient temperatures at which resting metabolic rate (MR) is at a minimum. While the TNZ lower limit has been characterized, it is still unclear whether there is an upper limit, that is, beyond which MR during rest increases, and if so, what physiological upregulations explain this. We take the first step to fill this knowledge gap by measuring MR and multiple physiological variables in participants exposed to ambient heat stress while resting. Thirteen participants were exposed for an hour to 28℃‐50% relative humidity (RH) air, and both 40 and 50℃ each in 25% RH and humid (50% RH) conditions. Core and skin temperatures, blood pressure, sweat‐, heart‐, and breathing‐rate, minute ventilation, and movement levels were recorded throughout each condition. MR increased 35% ( p = .015) during exposure to 40℃‐25% RH compared to baseline and a further 13% ( p = .000) at in 50℃‐50%RH. This was not explained by increased fidgeting ( p = .26), suggesting physiological upregulation. However, while greater heat stress invoked increases in heart rate (64%, p = .000), minute ventilation (78%, p = .000), and sweat rate (74%. p = .000) when comparing 50℃‐50% RH with baseline, the exact size of their relative energy cost is unclear and, therefore, so is their contribution to this increase in MR. Our study shows clear evidence that resting MR increases in humans at high temperature—there is a metabolic upper critical temperature, at least as low as 40℃. Further studies should pinpoint this value and fully explain this increased MR. Abstract : Little research has been performed to characterize the upper human thermoneutral zone (TNZ). To find out if the resting metabolic rate (RMR) increases above the TNZ, 13 participants were exposed to a series of hot ambient temperatures. Our study found that RMR did, indeed, increase and, thus, is the first to provide evidence of a metabolic upper critical temperature.